Survey for positively selected coding regions in the genome of the hematophagous tsetse fly Glossina morsitans identifies candidate genes associated with feeding habits and embryonic development - Lucas Freitas; Rafael D. Mesquita; Carlos G. Schrago (Genetics and Molecular Biology)
Abstract Tsetse flies are responsible for the transmission of Trypanossoma sp. to vertebrate animals in Africa causing huge health issues and economic loss. The availability of the genome sequence of Glossina morsitans enabled the discovery of several genes related to medically important phenotypes and novel physiological features. However, a genome-wide scan for coding regions that underwent positive selection is still missing, which is surprising given the evolution of traits associated with the hematophagy in this lineage. In this study, we employed an experimental design that controlled for the rate of false positives and we performed a scan of 3,318 G. morsitans genes. We found 145 genes with significant historical signal of positive selection. These genes were categorized into 18 functional classes after careful manual annotation. Based on their attributed functions, we identified candidate genes related with feeding habits and embryonic development. When our results were contrasted with gene expression data, we confirmed that most genes that underwent adaptive molecular evolution were frequently expressed in organs associated with key physiological evolutionary innovations in the G. morsitans lineage, namely, the salivary gland, the midgut, fat body tissue, and in the spermatophore.